2019
DOI: 10.1021/acs.chemrev.8b00408
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Catalytic Oxidation of Volatile Organic Compounds: A Review Based on Pollutant Sorts and Sources

Abstract: Recent advances in the catalytic oxidation of volatile organic compounds: a review based on pollutant sorts and sources. Chemical Reviews 119 (7) , pp. 4471-4568.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
740
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 1,611 publications
(749 citation statements)
references
References 1,175 publications
(2,714 reference statements)
3
740
0
6
Order By: Relevance
“…Propene has an extensive production and application in numerous industries, and it is a primary contributor to photochemical smog, making it unfriendly to the environment [117]. There are lots of reports focusing on the catalytic oxidation of propene.…”
Section: Selective Catalytic Oxidation Of Propenementioning
confidence: 99%
“…Propene has an extensive production and application in numerous industries, and it is a primary contributor to photochemical smog, making it unfriendly to the environment [117]. There are lots of reports focusing on the catalytic oxidation of propene.…”
Section: Selective Catalytic Oxidation Of Propenementioning
confidence: 99%
“…From a practical standpoint, every adsorbent has its limitation as regards its capacity at break through, necessitating its regeneration in situ. To ensure that no secondary pollutants are generated during regeneration, suitable catalytic materials should be chosen, balancing high VOC storage capacity on the one hand and ease of regeneration on the other …”
Section: Concluding Remarks and Prospectsmentioning
confidence: 99%
“…To ensure that no secondary pollutants are generated during regeneration, suitable catalytic materials should be chosen, balancing high VOC storage capacity on the one hand and ease of regeneration on the other. [27,57] Accordingly, selection of the adsorbent is the most crucial aspect. Based on the above discussion, it is suggested that the ideal candidate should have high adsorption capacity as well as strong bonding with the VOC(s) so as to ensure the VOC(s) are totally oxidized during regeneration before desorption can occur.…”
Section: Concluding Remarks and Prospectsmentioning
confidence: 99%
“…The release of VOCs may lead to a serious contamination to surface/ground water, and therefore it is of great significance to separate VOCs from contaminated water [4,5]. Various techniques including condensation [6], adsorption by porous materials [7], photocatalytic degradation [8,9], catalytic oxidation [10,11], membrane separation [4,12,13], air stripping in packed columns [5] and so on have been applied for VOCs removal from air or water at laboratory or industrial scale. Recently, membrane separation has drawn a great deal of attention due to the high effectiveness of VOCs removal by membrane techniques such as pervaporation and membrane distillation [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%